Dividend increases and initiations and default risk in equity returns - Charitou, Andreas; Lambertides, Neophytos; Theodoulou, Giorgos (My University, 2011)
This study extends the Grullon, Michaely, and Swaminathan (2002) analysis by incorporating default risk. Using data for firms that either increased or initiated cash dividend payments during the 23-year period 1986-2008, we find reduction in default risk. This reduction is shown to be a priced risk factor beyond the Fama and French (1993) risk measures, and it explains the dividend payment decision and the positive market reaction around dividend increases and initiations. Further analysis reveals that the reduction in default risk is a significant factor in explaining the 3-year excess returns following dividend increases and initiations.